2021
DOI: 10.3390/nu13124410
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption and Adult Diabetes Risk: A Systematic Review and Dose-Response Meta-Analysis

Abstract: (1) Background: Recent individual studies have demonstrated that consumption of ultra-processed food (UPF) may be related to type two diabetes mellitus (T2DM). We aimed to synthesize the results from these individual studies by conducting an updated systematic review and meta-analysis of observational studies evaluating the association between UPF consumption and the risk of T2DM. (2) Methods: A systematic search was conducted using ISI Web of Science, PubMed/MEDLINE and Scopus electronic databases from incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 56 publications
6
38
0
2
Order By: Relevance
“…The association between UPF and diabetes among this Chines population was consistent with the synthesized result of observational studies among adults in France, Netherland, UK, Spain, and Canada [ 13 ]. All studies applied the NOVA classification and four of them had follow-ups of 3.4–12 years [ 27 , 28 , 29 , 30 ] with HR/OR ranging from 1.13 to 1.53.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association between UPF and diabetes among this Chines population was consistent with the synthesized result of observational studies among adults in France, Netherland, UK, Spain, and Canada [ 13 ]. All studies applied the NOVA classification and four of them had follow-ups of 3.4–12 years [ 27 , 28 , 29 , 30 ] with HR/OR ranging from 1.13 to 1.53.…”
Section: Discussionsupporting
confidence: 87%
“…The evidence from the animal experiment indicates that UPF is a significant risk factor hyperinsulinemia and glucose intolerance [ 10 ], and certain types of UPF (e.g., soda and processed meats) were correlated with diabetes [ 11 , 12 ]. A recent meta-analysis of five observational studies from France, Netherland, Spain, UK, and Canada indicated each 10% increase UPF consumption was associated with the increased risk of diabetes by 15% in adults after adjusted for potential socioeconomic and lifestyle factors [ 13 ], while a cross-sectional study found among Brazil’s pregnant women that UPF intake was not associated with gestational diabetes mellitus [ 14 ]. There is no investigation of UPF intake and diabetes yet in China.…”
Section: Introductionmentioning
confidence: 99%
“…This literature is broadly growing, leading to the first reviews and meta-analyses summarizing findings from prospective studies and consistently showing associations between UPF consumption and increased risk of many non-communicable diseases (4,(7)(8)(9)(10)(11)(12)(13). Most of the studies are based on the NOVA classification distinguishing unprocessed, minimally processed, processed and ultra-processed foods (6).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Cuevas-Sierra et al [5] also refers to studies that show an association between the degree of ultra-processed food and various diseases. Systematic reviews have been written that examine the connection between ultra-processed foods and health effects, however, thus far not focusing on the intestinal bacterial flora in particular [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%